2004
DOI: 10.1074/jbc.m313349200
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Proteins by Isoketal-containing Oxidized Phospholipids

Abstract: Oxidative stress frequently leads to altered function of membrane proteins. Isoketals are highly reactive products of the isoprostane pathway of free radical-induced lipid peroxidation that rapidly form covalent protein adducts and exhibit a remarkable proclivity to form protein cross links in vitro. Examination of isoketal adducts from an animal model of oxidative injury revealed that initial adducts were formed by isoketals esterified in phospholipids, representing a novel oxidative injuryassociated modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 25 publications
(28 reference statements)
1
73
0
Order By: Relevance
“…Oxidation of PUFAs in lipoproteins is known to yield a complex array of products, both protein-bound and free in solution, including isoprostane-derived levuglandin (27,28) and isoketal (29,30) derivatives and numerous keto and hydroxy fatty acids (11). A range of smaller, more polar aldehydes, ketoaldehydes, alkenals, and hydroxyalkenals are also released into solution and react with protein to form Schiff bases, Michael adducts, and pyrrole and pyridinium compounds that contribute to the brown color, fluorescence, and cross-linking of oxidized lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of PUFAs in lipoproteins is known to yield a complex array of products, both protein-bound and free in solution, including isoprostane-derived levuglandin (27,28) and isoketal (29,30) derivatives and numerous keto and hydroxy fatty acids (11). A range of smaller, more polar aldehydes, ketoaldehydes, alkenals, and hydroxyalkenals are also released into solution and react with protein to form Schiff bases, Michael adducts, and pyrrole and pyridinium compounds that contribute to the brown color, fluorescence, and cross-linking of oxidized lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of total IsoK-lysyl-lactam adduct were then measured as previously described. 17,21 In brief, after treatment with 0.2N sodium hydroxide for 2 hours to hydrolyze esterified isoketals, protein was initially subjected to complete proteolytic digestion. After digestion, 500 pg of a ( 13 C 6 )-IsoK-lysyl-lactam internal standard was added to each sample, and IsoK-lysyl-lactam adducts were then quantified after solid phase extraction and an initial preparative HPLC by selective reaction monitoring LC electrospray tandem mass spectrometry for the transition from m/z 479 to 84 and m/z 485 to 89 (internal standard).…”
Section: Analysis Of Reactive Products Of Lipid Peroxidationmentioning
confidence: 99%
“…16 The hypothesis that alteration in cardiac ion channel function by free radical-mediated lipid peroxidation is potentially caused by the formation of IsoKs is supported by our recent finding that IsoKs formed in membrane phospholipids adduct to proteins while still esterified, suggesting that membrane proteins are a preferred target for adduction by IsoKs. 17 Moreover, these studies demonstrated that IsoKs dramatically inhibited the function of the delayed rectifier potassium current I Kr in cultured atrial tumor cell line 1 (AT-1) myocytes.…”
mentioning
confidence: 99%
“…Levels of γKA adducts significantly increase in pathological conditions including atherosclerosis, end-stage renal disease, and Alzheimer's Disease (5,6). Increased γKA adduct formation has also been characterized in experimental models of oxidative injury and inflammation, including carbon tetrachloride treated rats (7), hyperoxia treated mice (8), septic mice (9), and ex vivo activation of platelets (10). Levels of γKA adducted proteins are expected to be elevated in a wide variety of conditions previously linked to oxidative injury and inflammation (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…PM is quite hydrophilic, and we have previously found that IsoK formation initially occurs in situ on membrane phospholipids (7). Therefore, modification of PM in a way that retained its high reactivity but increases its lipophilicity could enhance its effectiveness as a scavenger.…”
mentioning
confidence: 99%